DISTRIBUSI ZAKAT PRODUKTIF DALAM PERSPEKTIF MAQASHID SYARIAH KONTEMPORER: TINJAUAN PUSTAKA TENTANG EFEKTIVITAS PENGENTASAN KEMISKINAN - Kamilatus Saidiyah; Mansur Mansur (Jurnal Ekonomi Syariah Darussalam, 2026)
This study aims to analyze the effectiveness of productive zakat distribution from the perspective of contemporary maqashid al-sharia through a literature review. The study employs a qualitative approach using library research and content analysis. The results show that the distribution of productive zakat contributes to increased income, the strengthening of microenterprises, and greater economic self-reliance among mustahik. However, the program’s effectiveness is significantly influenced by the quality of mentoring, business management capacity, the professionalism of zakat administrators, and a sustainable monitoring and evaluation system. From the perspective of contemporary maqashid al-sharia, productive zakat not only supports the preservation of the five fundamental objectives of sharia (maqashid al-sharia) but also realizes maslahah ‘ammah through improved welfare, social justice, and the transformation of mustahik into self-reliant individuals who may even become muzakki. This study concludes that the distribution of productive zakat will be more optimal if managed professionally through a business-cluster-based empowerment model, and evaluated using maqashid al-sharia-based indicators to ensure the achievement of poverty. Keywords: Productive zakat, Maqashid sharia, Poverty alleviation, Literature review.